Harmonization Of Procedural Law and Economic Substance Sharia In Dispute Resolution In The Religious Courts Religion - Banja Bakti Marantasi; Mutiara Apriliyani; Nara Sayuki (Faculty of Law, Muhammadiyah University of Surabaya, 2025)
This study examines the harmonization of procedural law with the substantive principles of Islamic economic law in the settlement of sharia economic disputes within Indonesia’s Religious Courts. The research addresses the gap between formalistic procedural mechanisms and the ethical, justice-oriented, and flexible nature of Islamic economic law. Using a normative juridical method with statutory, conceptual, and comparative approaches, the study analyzes Law Number 7 of 1989 on Religious Courts, as amended by Law Number 3 of 2006 and Law Number 50 of 2009, as well as Supreme Court Regulation (PERMA) Number 14 of 2016. It also compares Indonesia’s framework with sharia court practices in Malaysia and Brunei Darussalam. The findings indicate that existing procedural rules have not fully accommodated the objectives of Islamic law (maqāṣid al-sharī‘ah) and the principle of substantive justice (al-‘adl). Accordingly, procedural harmonization is required through22 the reformulation of procedural norms, strengthening judges’ interpretative authority as mujtahid qāḍī, and integrating maṣlaḥah mursalah into adjudication. Such reforms are expected to promote dispute resolution that ensures legal certainty while remaining consistent with the values and objectives of Islamic law.